Utilization Dishwashing Soap as a Subtitute of Xylol in the Deparaffinization process of Hematoxylin-Eosin Dye: Review Article: Penggunaan Sabun Pencuci Piring Sebagai Pengganti Xilol Dalam Proses Deparafinasi Perawarnaan Hematoksilin-Eosin - mamay, Mamay; Mutmaina, Gina Nafsa; Nurahma, Ina Aflaha (Universitas Muhammadiyah Sidoarjo, 2022)
Deparaffinization in the hematoxylin eosin staining process aims to remove paraffin from the tissue, clean the tissue and maximize dye absorption. Utilization xylol as deparaffinization has a drawback, if inhaled too much it will cause harm to the health of the laboratory staff. Considering this, a safer alternative to xylol is needed, one of which is dish washing soap. This study was conducted to determine the use of liquid dish soap at the deparaffinization stage on the quality of tissue staining results. The research method in this research is a literature review study conducted based on sources from several articles published digitally in the Science Direct, Pub Med, NCBI, Researchgate, Google Scholar with the keywords deparafinization, xylene, dish washing soap and Hematoxylin-eosin. Based on the results of a review of ten journals, the concentration of dishwashing soap used was 1.5%, 1.7%, 2% and 2.5% with the most widely used concentration of 1.7%. The most used deparaffinization time with dish soap was 1 minute, one study used 2 minutes. Of the several differences in deparaffinization time and concentration of dish soap, the results adequacy of nuclear and cytoplasmic staining, clarity, uniformity and crispness of staining were very good in almost all studies, there was no difference in quality with the use of xylol. So it can be concluded that the use of dish soap in the deparaffinization process for Hematoxylin staining showed good staining of all tissues. Dish soap can be used as an alternative agent in deparaffinization of Hematoxylin-Eosin staining.